Moral Justification of Organ Sale - Lepinová, Kristýna (Univerzita Pardubice, 2022)
Despite organ donation systems running in numerous states around the globe, the shortage of transplant organs is a worldwide public health problem. This raises a question, why - when there clearly is both demand and offer - not make organ sale legal? From the moral point of view, there are four main objections to permitting organ sale: 1. exploitation, commodification, and instrumentalisation of the seller and her body; 2. harm and risk that the seller undergoes; 3. concerns about autonomy and consent; and lastly, 4. concerns about the practice of free donation that would supposedly be undermined by the permission of organ sale.
Morální ospravedlnitelnost obchodování s lidskými orgány
Keywords: prodej orgánů; bioetika; lékařská etika; vykořisťování; komodifikace; instrumentalizace; újma; autonomie; souhlas; darování orgánů; altruismus; organ sale; bioethics; medical ethics; exploitation; commodification; instrumentalisation; harm; autonomy; consent; organ donation; altruism